2018
DOI: 10.3390/environments5030040
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to Climate Change: Lessons from Farmers and Peri-Urban Fringe Residents in South Australia

Abstract: This paper reports on results from two major research projects conducted in South Australia. The first investigates adaptation to climate change in two of the state's major grain and sheep farming regions, using semi-structured interviews and focus groups. The second uses a postal questionnaire and an internet-based survey of residents in the peri-urban fringes of Adelaide, the state capital, to examine knowledge of and attitudes to climate change and resulting adaptations, especially in the context of increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The respondents to the present survey felt that they would benefit from awareness raising and training in connection with climate change, which would certainly have an effect on the implementation of potential adaptation measures. Even though this segment was not part of the study, it should be noted that a common trait of farmers worldwide is that they will implement adaptation measures and accept training, if available (Robinson et al, 2018;Masud et al, 2017;Khatri-Chhetri et al, 2017). Training should be organized on a regional level, to present the latest advances in climate-smart agriculture, which facilitate adapting to climate change.…”
Section: Resultsmentioning
confidence: 99%
“…The respondents to the present survey felt that they would benefit from awareness raising and training in connection with climate change, which would certainly have an effect on the implementation of potential adaptation measures. Even though this segment was not part of the study, it should be noted that a common trait of farmers worldwide is that they will implement adaptation measures and accept training, if available (Robinson et al, 2018;Masud et al, 2017;Khatri-Chhetri et al, 2017). Training should be organized on a regional level, to present the latest advances in climate-smart agriculture, which facilitate adapting to climate change.…”
Section: Resultsmentioning
confidence: 99%
“…An inductive approach with much focus on mixed sampling was used to select respondents [18]. The adoption of an inductive approach did not negatively influence the results of the study because when studying barriers to climate change adaptation, one can obtain new insights not based on a specific pre-determined theory but from a systematic approach [19]. Likewise, multiple data sources [20] were triangulated to ascertain the views expressed by respondents in each case.…”
Section: Methodsmentioning
confidence: 99%
“…Long-serving Agricultural Technical and Extension Services (AGRITEX) officers helped the researchers to select smallholder farmer participants who were abundantly endowed with knowledge related to the local climate change history. A supplementary FGD session was rescheduled and administered in Wards 4,6,18,19,and 20 to make a full complement. For this study, the rationale for running extra FGDs was defined by some outstanding characteristics that were twofold.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an investigation into farmers' adaptations to climate change in South Australia, it was observed that most farmers interviewed did not believe in human-induced climate change. However, they acknowledged the occurrence of periods of excessive heat and/or drought and responded to these risks alongside others that affected their livelihoods, e.g., fluctuating prices, pests, changes to policy (Raymond & Robinson, 2013;Robinson et al, 2018). was the communities of practice that were the principal influence on the farmers as it was through these that farmers shared best practice and could learn from initiators of innovation in their local area.…”
Section: Agriculture and Climate Changementioning
confidence: 99%